SEMIOTIC IN “A MILD GO AHEAD” VERSION ON TELEVISION - Habibullah Habibullah; Zainuddin Zainuddin (State University of Medan, 2014)
ABSTRACT This research focused on semiotic used in A Mild Go Ahead. The aims are to find the use of semiotic and identify the meaning in A Mild Go Ahead.The data werethree television advertisements from A Mild Go Ahead entitled “Satu Aksi = Segalanya, We Are One and Free, and Orang Pemimpi. The researchwas conducted by using descriptive qualitative research.The findings show that there were three elements of semiotic used, such as representamen (qualisign, sinsign, legisign), object (icon, index, symbol), and interpretant (rheme, decisign, argument),which then devided into 9 types of semiotic;Qualisign (0),Legisign (9), Sinsign (34), Icon (12), Index (27), Symbol (4), Rheme (9), Decisign (19) and Argument (16). The most dominant type of semiotic in the advertisements is sinsign, and it means that A Mild Go Aheadpersuade their audiences by showing the real example of their products. Keyword : Semiotic, A Mild Go Ahead, Advertisement.